The Effect Cautins Fermeted Dragon Fruit Feel on The Carcass and Commercial Carcass Piece of Lohman Brown at 22 Weeks Age - I M. B., Jaya; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the effect of rations containing fermented dragon fruit peel on carcass and commercial carcass piece of Lohmann Brown chicken carcasses aged 22 weeks. This research was carried out at the Teaching Farm of the Faculty of Animal Husbandry, Udayana University. Bukit Campus. Jimbaran. Badung. – Bali for 4 weeks. The design used was Completely Randomized Design (CRD) with three treatments namely: laying hens were given rations without fermented dragon fruit skins (R0), laying hens were given rations with 5 % fermented dragon fruit skins (R1), and laying hens were given commercial rations (R2). Each treatment was repeated five times, each replication consisted 3 Lohmann Brown chickens. The variables observed were cutting weight, carcass weight, carcass percentage, and percentage of commercial carcass cuts. The results showed that the treatments of R0, R1 and R2 were not significantly different (P> 0,05) on slaughter weight, carcass weight, carcass percentage, and the percentage of commercial carcass pieces in the back, wings, and thighs. In the chest percentage variable treatment R0 is higher than R1 and R2 is significantly different (P <0,05). From the results of the study it can be concluded that the chicken ted 5 % dragon fruit fermented feel did not affect slaughter weight, carcass weight, carcass percentage, but it affected the percentage of 22 week old Lohmann Brown chicken breast carcass. Keywords: Lohmann Brown chicken, carcass, dragon fruit feel, commercial carcass pieces.